Microstructural evolution of 3C-SiC exposed to simultaneous neutron irradiation and helium implantation - Hu, Xunxiang; Koyanagi, Takaaki; Zhao, Jiangtao; Yamamoto, Takuya; Katoh, Yutai (Journal of nuclear materials, 2018)
The synergism of transmutant helium and irradiation defects is critically important to understand the performance of SiC when in service in nuclear environments. In this study, we exposed 3C-SiC in contact with a 2 μm Ni foil to neutron irradiation at 500 °C to 29 dpa in the high flux isotope reactor to simulate the simultaneous introduction of helium and irradiation defects into SiC. The combination of TEM observations and thermal desorption measurements helps to elucidate the impact of helium on the microstructural evolution in 3C-SiC. Thermal helium desorption spectra from ion-implanted and neutron-irradiated SiC showed a completely different desorption behavior in terms of the peak position and helium desorption flux. The identification of possible helium trapping sites was attempted by applying the first order dissociation model to the measured thermal helium desorption spectra. TEM observations of the neutron-irradiated samples showed that the presence of helium facilitated the stabilization of the defect clusters and promoted the formation of visible helium bubbles in SiC subject to simultaneous neutron irradiation and in-situ He implantation. Following the subsequent heat treatment during the thermal desorption measurements, large faceted helium bubbles were found along grain boundaries in the neutron-irradiated SiC with in-situ He implantation, while the helium bubbles in the grain interior were relatively smaller than those found in the neutron-irradiated sample without in-situ He implantation due to the reduced mobility of He-defect clusters. The He contents contained in the neutron-irradiated samples were quantified based on the experimental data from TEM and thermal desorption measurements.